2015
DOI: 10.1037/a0035189
|View full text |Cite
|
Sign up to set email alerts
|

The step-father effect in child abuse: Comparing discriminative parental solicitude and antisociality.

Abstract: Objective: The greater risk of abusing a step-child than a genetically related child has been attributed to discriminative parental solicitude. We tested whether it is better explained by antisociality, whereby more antisocial fathers are more likely both to have step-children and to be generally more violent. Method: We studied police reports of assaults on children by 387 domestically violent men who had a minor child, and their bivariate association with genetic relatedness, offender antisociality, and oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Studies comparing the rate of stepchildren in familicides to the general population show that step relationships are overrepresented in the familicide samples (Wilson et al, 1995;Wilson & Daly, 1997). This finding is in line with research indicating that parents do not invest in stepchildren to the same degree as in biological children (Antfolk, FAMILICIDE: A SYSTEMATIC LITERATURE REVIEW 16 Karlsson, Söderlund, & Szala, 2017;Henretta, Van Voorhis, & Soldo, 2014;Kalil, Ryan, & Chor, 2014), and that children have a higher risk of becoming physically and sexually abused by a stepparent than by a biological parent (Archer, 2013;Daly & Wilson, 1985Hilton, Harris, & Rice, 2015;Sariola & Uutela, 1996). This "Cinderella effect" can be partially explained by parents being emotionally more close to biological children, and by evolutionary assumptions, stipulating that natural selection has promoted parental investment in biological children, as these, in contrast to stepchildren, share the parent's genetic material (Antfolk et al, 2017;Karlsson, Malén, Kaakinen, & Antfolk, 2018;Trivers, 1972).…”
Section: Offender and Victim Characteristicssupporting
confidence: 87%
“…Studies comparing the rate of stepchildren in familicides to the general population show that step relationships are overrepresented in the familicide samples (Wilson et al, 1995;Wilson & Daly, 1997). This finding is in line with research indicating that parents do not invest in stepchildren to the same degree as in biological children (Antfolk, FAMILICIDE: A SYSTEMATIC LITERATURE REVIEW 16 Karlsson, Söderlund, & Szala, 2017;Henretta, Van Voorhis, & Soldo, 2014;Kalil, Ryan, & Chor, 2014), and that children have a higher risk of becoming physically and sexually abused by a stepparent than by a biological parent (Archer, 2013;Daly & Wilson, 1985Hilton, Harris, & Rice, 2015;Sariola & Uutela, 1996). This "Cinderella effect" can be partially explained by parents being emotionally more close to biological children, and by evolutionary assumptions, stipulating that natural selection has promoted parental investment in biological children, as these, in contrast to stepchildren, share the parent's genetic material (Antfolk et al, 2017;Karlsson, Malén, Kaakinen, & Antfolk, 2018;Trivers, 1972).…”
Section: Offender and Victim Characteristicssupporting
confidence: 87%
“…Evolutionary theorists (e.g., Archer, 2013;Daly & Wilson, 1996, 2008Hilton, Harris, & Rice, 2015) have reported that abuse occurs more often in step relationships than in genetic parentchild relationships. In this study we analyzed data from Klevens et al (2000) that have been cited in support of this claim (Archer, 2013;Daly & Wilson, 2001, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…A selectionist account would predict that fathers discriminate in favor of their genetic children, whereas an ecological account would predict that, all else being equal, genetic and stepchildren are equally at risk for abuse. Hilton, Harris, and Rice (2015) examined the records of 118 such men and found that 16 had abused their stepchildren, and 9 their genetic children. This indicates that fathers were approximately twice as likely to abuse their stepchildren as their genetic children.…”
Section: Discussionmentioning
confidence: 99%
“…The theory on preferential investment in biological children has received support from empirical research where adults have been found to be willing to invest more in biological children compared with stepchildren (e.g., Anderson, Kaplan, Lam, & Lancaster, 1999; Antfolk, Karlsson, Söderlund, & Szala, 2017; Henretta, Van Voorhis, & Soldo, 2014; Kalil, Ryan, & Chor, 2014; Zvoch, 1999). In addition, stepparents are overrepresented as perpetrators of physical and sexual abuse toward their stepchildren, and the rate of child homicide is higher in step relationships compared with biological relationships (Archer, 2013; Hilton, Harris, & Rice, 2015; Sariola & Uutela, 1996).…”
Section: Perpetrator–victim Relationshipmentioning
confidence: 99%